ANALISIS KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PADA PT. JANEETA DKI JAYA KOTA MEDAN - Indah Sari Liza Lubis (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2018)
The purpose of this study was to analyze the competence of human resources namely knowledge, skills, self-concept, traits, and motives affecting the performance of employees at PT Janeeta DKI Jaya Medan. Based on the results of the study, partially shows that: 1) Knowledge competency has a significant influence on employee performance; 2) Skills competencies have a significant influence on employee performance; 3) Self-concept competence has a significant influence on employee performance; 4) Competency traits have a significant influence on employee performance; 5) Competence motives have a significant influence on employee performance. Simultaneously that together, namely knowledge, skills, self-concept, traits, and motives affect the performance of employees at PT. Janeeta DKI Jaya Medan City..